Integrating ChatGPT in English Culture Courses: Opportunities, Challenges, and Pedagogical Implications - Moch Dheandra Al Reyva (Universitas Negeri Medan, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed various sectors, including education. One of the most promising AI tools is ChatGPT, which provides interactive, contextual, and adaptive learning experiences for students. This study aims to analyze the influence of ChatGPT as a learning medium in the English Culture in ELT course at Universitas Negeri Medan. Using a mixed-methods approach, data were collected from 50 English education students through observation, interviews, and questionnaires. The questionnaire results revealed that 78% of respondents agreed and 16% strongly agreed that ChatGPT assists them in completing academic tasks effectively. Furthermore, the average mean score across all items was 2.85, indicating a generally positive perception toward ChatGPT use. Most students reported that ChatGPT enhanced their understanding of English culture and provided innovative ideas for lesson planning. However, some respondents noted limitations such as dependence on AI and insufficient critical thinking stimulation. Overall, the findings demonstrate that ChatGPT positively contributes to learning engagement, comprehension, and creativity. It can serve as an effective supplementary tool for independent and culturally contextual English learning, provided that its use is accompanied by proper pedagogical guidance and digital literacy awareness.